Effects of reproductive seasonality on the excretion of fecal glucocorticoid metabolites in free-ranging Pampas Deer - Grotta-Neto, F. [UNESP] (2024)
Understanding how fecal glucocorticoid (GC) concentration is associated with reproduction in wild animals allows us to associate physiological stress with the costs of reproduction. Glucocorticoids are among the main stress-related hormones, and their secretion is strongly associated with reproductive seasonality. Using non-invasive methods (thereby avoiding causing stress), we used fecal GC metabolites (FGC) to test the hypothesis that the reproductive phase (mating, non-mating, gestation, and lactation) influences stress levels of the seasonally reproductive Pampas Deer (Ozotoceros bezoarticus). Furthermore, we compared FGC between sexes and between males of different antler statuses (velvet, hard, cast). During 1 year, in the Pantanal of Brazil, we collected 621 fresh fecal samples (327 from females, 294 from males) from which we estimated FGC using enzyme immunoassay (EIA). FGC concentrations varied by reproductive phase and antler status. Agonistic and courtship interactions associated with mating (i.e., fights between males, attempts to mount females), suggest that they influence FGC concentrations most strongly in both sexes. Females also had greater FGC concentrations during lactation, suggesting that this phase and parental care are also associated with increased physiological stress. In males, the association of FGC concentrations with antler status may be, in part, associated with photoperiod and testosterone secretion, both of which can trigger reproductive and agonistic behaviors. Finally, reproductive synchrony of the sexes causes similar FGC over time and suggests that environmental factors contribute as well. We show that non-invasive monitoring of glucocorticoid metabolites levels is an effective tool for detecting changes in the physiological stress response in Pampas Deer, suggesting that this tool will be useful for detecting changes in physiological stress caused by human disturbance, such as cattle ranching in Pantanal and similar disturbances elsewhere.